TOLERATING STRUCTURAL AMBIGUITY IN GRAMMAR LEARNING - Monika Dini Kurniasari (IJIET (International Journal of Indonesian Education and Teaching), 2017)
Teaching grammar is believed to be a way to help learners use English correctly and appropriately. However, as English teachers, we sometimes find that a word, phrase, or sentence is ambiguous as it has more than one meaning. The ambiguity, however, can be noticed if one really has a linguistic knowledge on how to analyze the phrase or sentence. There are two kinds of ambiguity (lexical and structural). This paper explores structural ambiguity. Structural ambiguity occurs when a phrase or sentence has more than one underlying structure. The phrase can be disambiguated by putting it in a sentence with some sort of formal indicator which helps the reader or hearer to recognize the sentence structure. Some of the signals include function words, inflections, affixes, stress, juncture, and punctuation. The rest of this paper discusses some types of structural ambiguity, how they differ, and some possible ways to resolve them in order to have understanding for the learners.DOI:https://doi.org/10.24071/ijiet.2017.010108